2012
DOI: 10.1590/s0104-11692012000100021
|View full text |Cite
|
Sign up to set email alerts
|

Presenteeism in hospital nurses

Abstract: This quantitative, descriptive, cross-sectional research aimed to determine the estimated productivity of health-related limitations at work in 129 nurses working in direct care delivery to critical and potentially critical patients. Instruments were applied for socio-demographic and functional characterization and for the evaluation of presenteeism (Work Limitations Questionnaire). Statistical Package for the Social Sciences software was used for data analysis. In this study, 75% of nurses obtained a lost pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 15 publications
5
30
0
5
Order By: Relevance
“…In terms of coping, the control dimension of coping was prevalent among the nursing staff, similarly to another Brazilian study (27) . This finding corroborates the results that showed that the participants assessed work-related stressors as positive events and used adequate coping strategies to deal with these situations.…”
Section: Discussionsupporting
confidence: 67%
“…In terms of coping, the control dimension of coping was prevalent among the nursing staff, similarly to another Brazilian study (27) . This finding corroborates the results that showed that the participants assessed work-related stressors as positive events and used adequate coping strategies to deal with these situations.…”
Section: Discussionsupporting
confidence: 67%
“…and refers to questions such as lack of recognition, autonomy, and the indefiniteness of the profession, impotence facing the situations, aspects of the physical environment and institutional organization (see Table 1). The Factors Intrinsic to the Work, third category of the inventory, is composed by 10 items (1,4,5,6,7,8,9,10,12,14) which deal with the working functions performed, such as working hours and inadequate resources [5] . The ISN allows measuring the general occupational stress of the nurse based on the averages of scale's items.…”
Section: Methodsmentioning
confidence: 99%
“…So, the use of problem-focused strategies, considered the more effective to lead to stressors from occupational context, may be not useful or effectives, causing a higher level of stress in nurses of nephrology units and impacting on their health, on productivity and on nursing care quality. This linkage between medical conditions, including stress, and productivity loss is inserted in the concept of presenteeism, described as a condition in which people attend to work environment, but the tasks included in workers' role are performed of a nonproductive way, i.e., there is not a good performance due to physical and mental illness related to work process [14] .…”
mentioning
confidence: 99%
“…Of these, musculoskeletal system diseases were the most common among nursing professionals (8,13) . Also, with respect to predisposing factors for health problems, one study asserted that employees came to work mentally and physically willing, but left mentally and physically unwell (14) . Another factor deemed by nursing managers as contributing to absenteeism involved personal relationships.…”
Section: Discussionmentioning
confidence: 99%